2017
DOI: 10.1017/s0950268817001686
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Kobe-type and Otsu-typeBabesia microtiin wild rodents in China's Yunnan province

Abstract: Babesiosis is an emerging tick-transmitted zoonosis prevalent in large parts of the world. This study was designed to determine the rates of Babesia microti infection among small rodents in Yunnan province, where human cases of babesiosis have been reported. Currently, distribution of Babesia in its endemic regions is largely unknown. In this study, we cataloged 1672 small wild rodents, comprising 4 orders, from nine areas in western Yunnan province between 2009 and 2011. Babesia microti DNA was detected by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…Additionally, further consideration should be given for any patient exposures to certain ecological habitat types-specifically broad-leaved forest, shrub, and cropland-as this study has shown that such exposure is considered to be an important risk factor (Tables 3 and 4). Ecological habitat type of forest was also found to be an important risk factor for B. microti infection in other studies in Yunnan [26,27] and in Southeast Asia [28]. Thus, these findings show that forests, the natural habitat for ticks, likely represent areas of high risk for transmission of B. microti to humans, and as such, people either working in or traveling to the forest, should utilize adequate protection.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Additionally, further consideration should be given for any patient exposures to certain ecological habitat types-specifically broad-leaved forest, shrub, and cropland-as this study has shown that such exposure is considered to be an important risk factor (Tables 3 and 4). Ecological habitat type of forest was also found to be an important risk factor for B. microti infection in other studies in Yunnan [26,27] and in Southeast Asia [28]. Thus, these findings show that forests, the natural habitat for ticks, likely represent areas of high risk for transmission of B. microti to humans, and as such, people either working in or traveling to the forest, should utilize adequate protection.…”
Section: Discussionsupporting
confidence: 66%
“…To our best knowledge, the greater long-tailed hamster (Tscherskia triton), has not been reported for B. microti infection before, while the other seven species involved in this study were reported in previous studies to serve as probable reservoir hosts for B. microti [11,26,[31][32][33][34]. Our findings indicate the potential role of Tscherskia triton, with such a high infection rate of 33.3% (Table 2), for maintaining an enzootic cycle of B. microti, but further detailed studies are needed to confirm whether it is a reservoir host, an occasional host, or even an enhancing host.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…which is efficiently affected humans through ticks infestation [7]. Babesia microti has been identified in rodents and can efficiently affect human [8,9]. Camel babesiosis is an acute to chronic infectious disease that is distributed all over the world [2].…”
Section: Introductionmentioning
confidence: 99%